The Speech Act of Explanation in Closure Signs - 이혜경 (사회언어학, 2023)
This study investigates the speech act of explanation within a corpus of approximately 243 closure signs posted during the Covid-19 pandemic in Korea. Using a classification system derived from Bella and Ogiermann (2022), the explanations are categorized into four distinct groups. Category 1 explanations are further divided into three subcategories: signs revealing the relationships between government decisions and closures, those with expressions of support for official mandates, and those presenting dissent with closure directives. A comparative analysis between the third sub-category and pandemic-related activities (i.e., My Body My Choice Activities) is also conducted, highlighting similarities and differences. Category 2 centers on safety concerns, emphasizing public health and safety as the primary justification for closures. Notably, this category showcases an elevated sense of agency among sign authors. Explanations in Category 3 combine Categories 1 and 2. Category 4 explanations, which attribute closure to Covid-19, necessitate an investigation of terms referring to Covid-19. It is observed that the naming closely adheres to normative and public guidelines, reflecting a collective awareness of the crisis and a commitment to cooperation. The findings contribute valuable insights into the linguistic and cultural characteristics of explanations within Korean business closure signs, indicating phenomena specific to Korean communities.
Keywords: closure signs; speech acts; explanation; Covid-19; crisis communication